Strategies in Teaching Vocabulary for the 8th-grade Students: A Case Study at SMP Dwijendra Mataram in Academic Year 2024/2025 - Crismeilani, Kadek; Melani, Boniesta Zulandha; Saputra, Agus; Amin, Muhammad (Journal of Classroom Action Research, 2025)
This study aims to identify and describe the strategies used by the English teacher in teaching vocabulary to eighth-grade students at SMP Dwijendra Mataram in the 2024/2025 academic year. The school was selected as the research site because the researcher had direct teaching and observational experience during a four-month Kampus Mengajar program at the school. During the program, several challenges were observed in vocabulary learning, including students' low interest in reading, difficulties in memorizing words, and diverse student backgrounds. A qualitative descriptive method with a case study approach was used. Data were collected through classroom observations and semi-structured interviews with the English teacher. The results showed that the teacher implemented three main strategies: formal practice (structured activities such as repetition and drilling), functional practice (context-based learning related to daily life), and memorization strategies (using visual media such as videos). These strategies were proven to improve students’ vocabulary mastery while also increasing their motivation and engagement in learning English.